2013
DOI: 10.1002/term.1729
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and physicochemical,in vitroandin vivoevaluation of an anisotropic, nanocrystalline hydroxyapatite bisque scaffold with parallel-aligned pores mimicking the microstructure of cortical bone

Abstract: Scaffolds for bone regeneration are mostly prepared with an isotropic, sponge-like structure mimicking the architecture of trabecular bone. We have developed an anisotropic bioceramic with parallel aligned pores resembling the honeycomb arrangement of Haversian canals of cortical bone and investigated its potential as a scaffold for tissue engineering. Parallel channel-like pores were generated by ionotropic gelation of an alginate-hydroxyapatite (HA) slurry, followed by ceramic processing. Organic components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…the sealing zone) that delimits the resorbing area onto which osteoclasts generate an acid milieu that can reach values below pH 3, resulting in the dissolution of the underlying mineral [36]. In this regards, studies performed at low pH can be used as predictors of osteoclastic degradation [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…the sealing zone) that delimits the resorbing area onto which osteoclasts generate an acid milieu that can reach values below pH 3, resulting in the dissolution of the underlying mineral [36]. In this regards, studies performed at low pH can be used as predictors of osteoclastic degradation [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…The present study demonstrated the feasibility of directed ionotropic gelation of alginate to fabricate cellladen biphasic constructs with an anisotropic pore structure mimicking osteochondral tissue. This method was previously applied to fabricate constructs for bone tissue engineering (Dittrich et al, 2007;Bernhardt et al, 2009;Despang et al, 2013). The first steps to adapt this process to osteochondral tissue engineering were already taken in 2007 (Gelinsky et al, 2007) and are being continued with regard to the embedding of living cells during alginate gelation and are being investigated in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…Although other processing methods are also being explored—parallel channel‐like pores, for example, were generated by directed ionotropic gelation of alginate–hydroxyapatite (HA) slurry, followed by thermal removal of alginate—additive manufacturing techniques are drawing the majority of research efforts, mainly due to the increased availability of equipment and their improved resolution.…”
Section: Introductionmentioning
confidence: 99%